Examination of the Correlation Between Physical Education Teachers' Levels of Happiness and Psychological Well-being (Diyarbakır Province) - Hamdullah Ateş (Türk Spor ve Egzersiz Dergisi)
In this study, it is aimed to determine the relationship between these two variables by examining the happiness and psychological well-being levels of physical education teachers in terms of different variables. The sample group of this research consisted of 252 physical education teachers working in schools affiliated to the Ministry of National Education in Diyarbakır. Oxford Happiness Scale and Psychological Well-Being Scale were used as data collection tools. According to the findings obtained in the study, it was determined that the happiness and psychological well-being levels of physical education teachers were above the medium level. It was observed that the happiness and psychological well-being levels of physical education teachers did not differ according to gender, but differed according to age. In the comparison between physical education teachers' sports, exercise or physical activity status and happiness and psychological well-being, it was seen that there was a significant difference in favor of those who did sports, exercise or physical activity. While it was determined that there was a significant difference in favor of those participating in social activity in the psychological well-being levels of physical education teachers participating in social activities, it was seen that there was no difference between the happiness levels of physical education teachers and their participation in social activities. It was determined that there was a significant difference between the happiness and psychological well-being levels of physical education teachers and their self-identification in daily life in favor of the teachers who stated that they were peaceful and calm. As a result, it has been determined that there is a moderate and positive relationship between teachers' happiness levels and psychological well-being levels.